Emergency Department Recognition of Delirium: Quality Improvement Towards a Geriatric-Friendly ED - Mona AlGharibi; Mohammad Anzal Rehman; David Curran; Elsa Madott; Asim Islam; Rishi Prasad (Saudi Journal of Emergency Medicine)
Introduction: Delirium is a common yet often undetected condition in the elderly, particularly in the Emergency Department (ED). Its subtle presentation makes timely recognition challenging. Literature shows up to 10% of older patients presenting to the Emergency Department will have Delirium, but typically only 30% of these cases are identified in the Emergency Department. Aims/Objectives: To implement quality improvement measures for early recognition of delirium in geriatric patients aged 65+ in a single center ED. Specific objectives include staff training on delirium identification, enhancing screening protocols, and implementing interventions to address delirium promptly. Materials/Methods: ED staff providers underwent systematic training to optimize integration of Delirium Triage Screening (DTS) and Confusion Assessment Method (CAM), customized to the UAE patient population, into the geriatric ED workflow. A multidisciplinary team consisting of Geriatrics, Internal Medicine, ED Staff Physicians & Nurses established Quality Improvement Projects as part of a transition to a geriatric-friendly ED. Patients diagnosed with Delirium were retrospectively studied across 3 months to assess for use of DTS and CAM in ED evaluation. Results: The collected data demonstrates a small percentage of patients with a diagnosis of Delirium. Given that the average frequency of Delirium tends to be around 10% in geriatric patients presenting to the ED, the presence of Delirium at our ED at 0.97% may represent a possible under-diagnosis of the condition. Documentation for both DTS and CAM was suboptimal, well below the target of at least 90%. While the policy prepared was comprehensive, communication of the recognition and assessment pathways could be improved. Discussion: Following suboptimal initial results, dedicated internal departmental learning lectures were organized that focused specifically on the DTS and CAM assessments, with ample time for questions and answers with discussion to best understand and integrate these assessments into our ED workflow. Conclusion: An improved understanding of Delirium, followed by an enhanced integration of validated screening tools will invariably improve ED recognition of Delirium, thereby improving patient-oriented outcomes for elderly individuals presenting to the ED. [SJEMed 2024; 5(1.100): S24-S24]